2006
DOI: 10.1530/eje.1.02280
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclooxygenase-2 in orbital fibroadipose connective tissues of Graves’ ophthalmopathy patients

Abstract: Objective: The aim of this study is to evaluate the expression of cycloocygenase-2 (COX-2) in orbital fibroadipose connective tissue in Graves' ophthalmopathy (GO) patients, and investigate the associations between COX-2 expression and GO characteristics. Methods: The orbital fibroadipose connective tissues of 23 cases demonstrating moderate or severe GO, and eight control subjects without any history of thyroid or autoimmune disease were analyzed for COX-2 mRNA expression. Real-time relative quantitative PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…71 This enzyme is upregulated in the orbit of patients with Graves’ ophthalmopathy, 72 and T cells from such patients produce prostaglandins that induce adipogenesis in orbital fibroblasts. 73 Thyrotropin can stimulate adipogenesis in mouse embryonic stem cells, even in the absence of other adipogenic factors, suggesting that activation of the thyrotropin receptor initiates new fat-cell development.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…71 This enzyme is upregulated in the orbit of patients with Graves’ ophthalmopathy, 72 and T cells from such patients produce prostaglandins that induce adipogenesis in orbital fibroblasts. 73 Thyrotropin can stimulate adipogenesis in mouse embryonic stem cells, even in the absence of other adipogenic factors, suggesting that activation of the thyrotropin receptor initiates new fat-cell development.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…At the heart of this response is an exaggerated induction of prostaglandin endoperoxide H synthase-2 (PGHS-2), the rate limiting, inflammatory cyclooxygenase involved in the production of PGE 2 [14]. PGHS-2 has been found over-expressed in orbital tissues from patients with TAO [15]. Moreover, both B and T cells have substantial capacity to generate PGE 2 through the induction of PGHS-2 which occurs in their activated states [16]–[18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that selenium was able to reduce H 2 O 2 -mediated expression of COX-2 in vascular endothelial cells by inhibiting the p38 MAPK pathway [51]. …”
Section: Mechanisms Of Selenium Action In Gd and Gomentioning
confidence: 99%